590. GERD AND BARRETT`S ESOPHAGUS IN BARIATRIC SURGERY. (24th September 2022) - Moulla, Yusef; Feisthammel, Jürgen; Blüher, Matthias; Gockel, Ines; Dietrich, Arne
Abstract: The role of preoperative Gastroscopy in obesity surgery in detecting a lot of abnormalities of Upper-GI such as GERD and BE`s has been already proved in our pervious study. The Development of GERD and BE`s after bariatric surgery still controversy in the bariatric surgery. The Aim of this study is to evaluate the development of GERD and BE`s in patients underwent bariatric surgery including LGB and LSG In our single center prospectively-established database of obese patients, who u nderwent bariatric surgery from 01/2012 to 12/2019, we retrospectively compare the preoperative endoscopic finding of patients with BE`s to these findings after 1-2 years and 3-5 years after the bariatric surgery. The regression of BE's was defined based on the endoscopic findings as a 1 cm down grade of Prague classification circumferential (C) as well as maximum extent (M) or complete regression of BE's, histologically as a conversion of intestinal metaplasia to squamous epithelium or conversion of dysplastic dysplasia to intestinal metaplasia Among 914 bariatric patients, we found 119 patients (13%) with BE`s. A control gastroscopy could be performed in 74 BE`s Patients. 37 patients received a control gastroscopy after 1-2 years and 47 patient after 3-5 years. The surgical procedure was the only significant factor for the development of GERD and BE`s after bariatric surgery (P< 0.05). Progression of GERD after LGB was detected only in one patient (4.2%, n=54) and in 10 patients (50%, n=10) after LSG in patients. Furthermore, the progression of BE`s after LGB in 4 patient (7.4%, n=54) and in 6 patients (30%, n=20) after LSG Laparoscopic gastric bypass should be considered in obese patients with GERD or BE`s. Therefore, detecting of GERD and BE`s prior to bariatric surgery may has an obvious impact on decision making regarding the suitable surgical bariatric procedure